Intracellular DNA sensing by neutrophils and amplification of the innate immune response - Mankan, Arun K.; Czajka-Francuz, Paulina; Prendes, Maria; Ramanan, Sriram; Koziej, Marcin; Vidal, Laura; Saini, Kamal S. (Frontiers in Immunology, 2023)
As the first responders, neutrophils lead the innate immune response to infectious pathogens and inflammation inducing agents. The well-established pathogen neutralizing strategies employed by neutrophils are phagocytosis, the action of microbicide granules, the production of ROS, and the secretion of neutrophil extracellular traps (NETs). Only recently, the ability of neutrophils to sense and respond to pathogen-associated molecular patterns is being appreciated. This review brings together the current information about the intracellular recognition of DNA by neutrophils and proposes models of signal amplification in immune response. Finally, the clinical relevance of DNA sensing by neutrophils in infectious and non-infectious diseases including malignancy are also discussed.